0
$\begingroup$

I have problems with CNF form of formula in boolean logic. I need to get it using only laws of boolean algebra.

The formula is:

$$(!a \land !b \land !c) \lor (!a \land !b \land d) \lor (b \land c \land !d) \lor (a \land c \land !d)$$

Thank you for your help guys!

$\endgroup$
0
$\begingroup$

To get you started: $(!a \land !b \land !c) \lor (!a \land !b \land d) \lor (b \land c \land !d) \lor (a \land c \land !d) \\ \Updownarrow \qquad\text{Distribute} \\ ((!a\land !b)\land(!c\lor d))\lor ((b\lor a)\land(c\land !d)) \\ \Updownarrow\qquad\text{DeMorgan}\\ (!(a\lor b)\land(!c\lor d))\lor ((b\lor a)\land !(!c\lor d)) \\ \Updownarrow\qquad\text{use }(!P\land Q)\lor(P\land !Q)\iff (!P\lor !Q)\land(P\lor Q)\\ (!(a\lor b)\lor !(!c\lor d))\land ((b\lor a)\lor (!c\lor d)) $

Can you take it from here?

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.